A CORPUS BASED STUDY ON THE USE OF ‘ETC’ IN ACADEMIC WRITING - WIDIASTUTI, SRI (BEBASAN Jurnal Ilmiah Kebahasaan dan Kesastraan, 2015)
Previous studies of words used in academic writing have resulted in the vocabulary list of academic English. This study aims at analyzing the use of the word ‘etc’, the abbreviation for ‘et cetera’, which does not belong to one of that list. It especially concerned with methodological issues relating to theaccurate measurement of the usage of that word in academic writing, in this case the data from the Corpus of Contemporary American English (COCA) and the British National Corpus (BNC). On the basis of findings, it can be concluded that despite the academic writing guidelines in several university’s writing centers in United States stating to avoid the use of ‘etc’ and substitute it with ‘and so forth’ in academic writing, the corpus data show that ‘etc’ used mostly in academic writingcompared to the other types of writing and more popular than the use of ‘and so forth’.